Research approaches to sustainable biomass systems - Tojo, Seishu (Academic Press, 2014)
Researchers, students and engineers working with biofuels and biomass are increasingly expected to comprehend a new holistic systems perspective that begins with wise crop breeding and cultivation techniques and informs the entire conversion to energy process. This volume provides diverse examples of successfully implemented sustainable biomass research in Asia, highlighting the challenges faced by designers of new biomass production facilities and tips on how to develop approaches to overcome them. In addition to providing an authoritative guide on the utilization of the authors' sample feedstocks, rice straw and sunflower, the authors provide lessons relevant to stakeholders involved with all manner of biomass production projects by drawing out important comparisons and contrasts that must be taken into account when deciding how to utilize biomass as an energy resource in a way that is economically feasible and environmentally sustainable. Provides diverse examples of successfully implemented biomass research, highlighting insights on common bottlenecks and approaches developed to overcome them. Features coverage of the full feedstock life cycle, from crop breeding to commercial application, focusing on 3 key areas: biomass production, biofuel conversion technologies, and sustainable practices. Examines two regionally compatible feedstock, rice-straw and sunflower, performing a compare and contrast analysis of agricultural production methods, economics, conversion systems, and environmental impacts.